Ethnostatistics of Single Integrated National Database: A Reflection on the National Program of Socioeconomic Registration for Social Protection Programs in Indonesia - Eko Wahyono; Pratiwi Pratiwi; Nuzul Solekhah; Dian Karinawati Imron; Fatwa Nurul Hakim; Nurbaety Setram; Risyanto Risyanto; Atqo Mardiyanto; Agus Pramono; Agus Eko Nugroho; M Alie Humaedi (Universitas Muhammadiyah Yogyakarta, 2024)
Lessons from participative de facto and de jure approaches to socioeconomic registration for integrated policymaking have been underexplored, especially in archipelagic states and middle-income countries. This study aims to analyze participants' perceptions of statistical data and assess how socioeconomic circumstances shape the Regsosek (socioeconomic registration) process in Indonesia. Using a qualitative method, the research incorporates ethnographic techniques and triangulation, with enumeration carried out by locals familiar with the socio-cultural characteristics of the communities. The data were validated through multiple cross-checking stages. The Regsosek initiative seeks to create a unified national database to improve policymaking, a key aspect of Indonesia's socioeconomic development that has received limited attention in terms of participative methods. While prior studies have focused on the technical aspects of socioeconomic data collection, this research highlights the influence of socioeconomic diversity on the process. Novel insights reveal that participants’ perceptions of well-being vary based on socioeconomic backgrounds, geographic conditions, livelihood systems, gender, and exposure to previous development programs. Key challenges identified include community resistance and misconceptions linking data collection to social assistance, as well as the need for system integration and stability to establish a single national database. The study concludes that development and poverty alleviation programs must be mutually agreed upon to avoid disruptions, instability, and political influence, offering a fresh perspective on integrated policymaking in archipelagic and middle-income contexts.